Consequences of β-Thalassemia or Sickle Cell Disease for Ovarian Follicle Number and Morphology in Girls Who Had Ovarian Tissue Cryopreserved - Mamsen, Linn Salto; Kristensen, Stine Gry; Pors, Susanne Elisabeth; Bøtkjær, Jane Alrø; Ernst, Erik; Macklon, Kirsten Tryde; Gook, Debra; Kumar, Ajay; Kalra, Bhanu; Andersen, Claus Yding (Frontiers in Endocrinology, 2021)
Women with β-thalassemia (BT) and sickle cell disease (SCD) have a high risk of infertility and premature ovarian insufficiency. Different fertility preserving strategies, including ovarian tissue cryopreservation (OTC) and oocyte cryopreservation has been considered, and the healthy first babies have been born after successful OTC and transplantation. We evaluated follicle number and follicle health in ovarian tissue from a cohort of BT and SCD patients who underwent OTC before the age of 18 years. Patients undergoing OTC from 2002-2019 were included. A total of 14 girls and adolescents with BT and 4 with SCD, aged 2.8-17.4 years at OTC were included together with a reference group of 43 girls and adolescents with non-anemia diseases considered to have normal ovaries aged 0.6-17.9 years at OTC. Ovarian follicle density was measured in cortex biopsies and compared to the reference group. Expression of proteins associated with follicular health was evaluated using immunohistochemistry. Follicles were detected in the ovarian cortex biopsies from all patients with BT and SCD. The follicle densities were within the 95% prediction interval of the reference group in all cases. A similar expression of 6 proteins essential for follicular health was detected using immunohistochemistry in BT, SCD, and references. OTC should be considered an option for young girls and adolescents with BT and SCD.